Performance of Islamic Teachers in Madrasah: Analysis of Problems and Solutions in the Learning Process - Basuki Basuki; Iyoh Mastiyah; Edi Irawan; Abd Aziz (AL-ISHLAH: Jurnal Pendidikan, 2024)
This study investigates the performance achievements of 60 Islamic teachers in madrasahs during the learning process and identifies the problems and solutions needed to ensure all teachers meet the standards set by the Decree of the Minister of Education, Culture, Research, and Technology of the Republic of Indonesia Number 209//P/2021. Utilizing a survey methodology and in-depth interviews, the study found several challenges: 19 teachers struggled with implementing contextual learning; 8 teachers faced issues with process and results assessment; 18 teachers had problems with remedial and enrichment programs; 15 teachers found it difficult to create a pleasant learning environment; 31 teachers encountered obstacles in promoting reading and writing literacy; 10 teachers had trouble ensuring student safety, comfort, and cleanliness; and 17 teachers faced difficulties optimizing school facilities and infrastructure. These challenges were attributed to the lack of active participation in teacher quality improvement training programs such as contextual teaching and learning, assessment instruments, active learning, literacy, and media and learning resource development training. Interviews with teachers who did not face these difficulties indicated that their participation in ongoing professional development programs helped them overcome these issues. Consequently, it is recommended that school stakeholders support teachers' involvement in these professional development programs to enhance their performance.